CHẤT LƯỢNG DỊCH VỤ VIỆC LÀM VÀ SỰ HÀI LÒNG CỦA NGƯỜI TÌM VIỆC TẠI TRUNG TÂM DỊCH VỤ VIỆC LÀM LÂM ĐỒNG - Hồ, Quang Thanh (Trường Đại học Đà Lạt, 2023)
This research discovers and affirms the components and factors that make up quality of service and the satisfaction of jobseekers at the Centre for Employment Service in Lamdong province (CESLD), accredited by structural equation modeling (SEM) based on the basis of theoretical models for measuring service quality of Parasuraman et al. (1988, 1991). The results showed that, the scale consisting of five components: (1) Reliability; (2) Responsiveness; (3) Assurance; (4) Empathy; and (5) Tangibles is an important factor in satisfying jobseekers. Moreover, the quality of service could explain 77% the satisfaction of job applicants at the CESLD.